68Ga-Labeled Anti–Prostate-Specific Membrane Antigen Peptide as Marker for Androgen Deprivation Therapy Response in Prostate Cancer. (May 2016) - Schlenkhoff, Carl Diedrich; Gaertner, Florian; Essler, Markus; Hauser, Stefan; Ahmadzadehfar, Hojjat
Abstract : Abstract: Prostate cancer was diagnosed in a 71-year-old man with an elevated prostate-specific antigen. The CT of the abdomen showed multiple para-aortal lymph nodes, and thus, a 68 Ga anti–prostate-specific membrane antigen (PSMA-11) PET/CT was initiated, which showed, aside from the prostate cancer and multiple iliacal and para-aortal lymph node metastases, an increased tracer uptake in a lymph node left cervical. According to this advanced disease, a palliative therapy with GnRH agonist was initiated. A second PSMA-11 PET/CT was performed 4 months later, which showed a very good response; thus, additional radiation of the pelvis and the draining lymphatic system was performed.